Syndemic Connections: Overdose Death Crisis, Gender-Based Violence and COVID-19 - Ana M. Ning (Societies, 2024)
This article will use syndemic theory to identify and analyze overlapping health and social conditions, focusing specifically on how gender-based violence is systemically interconnected with contemporary public health issues. The overdose death crisis that continues to afflict Canadian populations is not an isolated health issue. Across Canada, it is intertwined with mental health, HIV/AIDS, COVID-19 and structural violence—the chronic and systemic disadvantages affecting those living in poverty and oppressive circumstances. Opioid use is an often-avoidant coping strategy for many experiencing the effects of trauma, relentless fear, pain, ill health and social exclusion. In particular, Indigenous and non-Indigenous women’s experiences with opioid addiction are entangled with encounters with gender based-violence, poverty and chronic ailments within structurally imposed processes and stressors shaped by a history of colonialism, ruptured lifeways and Western ways of knowing and doing, leading to disproportionate harms and occurrences of illness. While biomedical models of comorbidity and mortality approach substance misuse, gender-based violence and major infectious diseases such as HIV/AIDS and COVID-19 as distinct yet compounding realities, this article argues that these conditions are synergistically interrelated via the critical/reflexive lens of syndemic frameworks. Through secondary research using academic, media and policy sources from the past decade in Canada, complemented by prior ethnographic research, the synergistic connections among opioid addiction, gender-based violence and the effects of the COVID pandemic on diverse women will be shown to be driven by socio-structural determinants of health including poverty, intergenerational trauma, the legacy of colonialism and Western optics. Together, they embody a contemporary Canadian syndemic necessitating coordinated responses.